Trust and credibility on the web: The relationship of web experience levels and user judgments - Jozsa, Eszter; Komlodi, Anita; Ahmad, Rahayu; Hercegfi, Karoly (2012)
The Internet as a source of information became extremely important among information seekers in recent years However, current Web technologies have created the opportunity for information producers to easily and anonymously publish information that can often be of questionable quality. Due to the absence of an editorial function (in most cases) users need to carefully consider the quality of their search results. Our current study reports findings about the relationship between users' web experience level and the credibility judgment criteria they used.